Experience using a project-based approach in an introductory programming course - Davenport, D. (IEEE transactions on education, 2000)
This paper describes how and why the authors' department chose to integrate a sophisticated visual programming environment (DELPHI) into the introductory programming course (CS101/2) of the first-year undergraduate engineering curriculum. It also reports on the outcome of this venture, which involved a switch from a conventional lecture-based approach to teaching CS102 to a project-based approach. While it meant more work for both students and teachers, the overall response from both parties was very positive. Indeed, the resulting designs and subsequent survey results seem to confirm that students achieved a better appreciation and understanding of the course's objectives.